Role of Ideology in Foreign Policy: A Case Study of Iran - Umbreen Javaid; Muhammad Arshad Watoo; Uzma Naz; Azhar Rashid (Journal of Political Studies, 2016)
The main purpose of the study is to analyze the role of Ideology and pragmatism in Iranian foreign policy. Main thesis is whether one factor surpasses the other while making the choices and decisions or both impacts equally influence the course of action in global political arena. The focus remains on the Iran’s foreign policy towards the western world in general and America in particular. It also focuses the role of cultural disparity and why constructive breakthrough has not been achieved previously. Moreover, the cordial relationship with United States has been held in abeyance due to ideological clash and policy priorities between the two states. Iran remained focused more on ideology rather giving attention to US strategic concerns in the region since the end of cold war. Diplomatic behaviors of the states are results of the historical animosities and cordialities among the states. Moreover, Iranian policy priority has been anti-hegemonic and antiimperialistic designs of the big powers in the post-cold war era. They kept their ideology alive and remained fixed on their strategic interests and ideology. Moreover, the scenario in the post 9/11 has been changing and global environment continue to be tougher for underdeveloped and the developing countries. Iran has been suffering due to unlimited economic and political bans because it is not bowing before the global superpower. However, things started changing and a shift came up in the policy of Iran with the emergence of new rapprochement in shape of a historical deal with United States. It seems the Iranian policy has tilted more on the side of pragmatism.